GST and its Influence on Hospitality - Prof. Shilpa Revankar (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
A comprehensive, multi-stage, destination-based tax on goods and services called the "Goods and Services Tax" will be imposed on every value addition. GST is recovered from the final consumer. All sorts of Indirect taxes like Excise duty, Service Tax, Octroi, Entry Tax, Entertainment Tax, Luxury Tax are merged under GST except a few taxes such as Basic customs duty, anti-dumping duty, safeguard duty, property tax, stamp duty and so on. The GST system went into effect in India on July 1st, 2017, with the slogan "one nation, one tax." and which will see its effects on different economic sectors. GST will have an impact on all industries, including the hospitality sector. It uses a dual structure concept to prevent cascade consequences. The GST is going to affect the suppliers and service providers as well as the consumers of the Restaurant Industry. In the earlier tax system Hotel industry was attracting the taxes such as VAT, Service Tax, Luxury tax, CST, Central excise etc.. But all these taxes are subsumed in to a singe tax under GST. Therefore there is a necessity to study the impact of GST on Hotel industry as well as on the consumers of this industry. This paper highlights the changes reflected in the hotel and restaurant industry due to transformation of old VAT and other tax systems in to the new GST system. The study is conducted in Dharwad District of Karnataka state. As this coastal district is the famous tourist and commercial Centre, more restaurants and hotels are emerging in this area.